The Incidence of Vaso-vagal Reactions Among Whole Blood Donors During or Immediately After Donation - Atiar Rahman; Jolly Biswas; Md Ashadul Islam; Ayesha Khatun; Nittyananda Shil; Sheikh Saiful Islam Shaheen; Zillur Rahman Bhuiyan (Bangabandhu Sheikh Mujib Medical University Journal, 2011)
Background: The incidence of vaso vagal reaction among the whole blood donors are common. Few percent of these reaction may progress to syncope.